Losing our minds to a machine - Abd Razak, Dzulkifli (2010)
A RECENT survey conducted by a company indicated that almost 90 per cent of Malaysian children who go online have had negative experiences. This ranged from harassment to being exposed to unwholesome images. However, many parents are unaware of them. Only 40 per cent supervised their children.